Associations between internal and external sexual consent in a diverse national sample of women. (15th October 2019) - Willis, Malachi; Blunt-Vinti, Heather D.; Jozkowski, Kristen N.
Abstract: Sexual consent can be conceptualized as an internal willingness to engage in sexual behavior. To communicate this internal feeling, people use and interpret cues—both active and passive. We proposed and tested a model for the potential mechanisms underlying women's sexual consent, which predicted associations between women's internal feelings of consent and the consent cues communicated and interpreted in a given sexual encounter. Because research on sexual consent has consistently urged researchers to collect data from samples that are not primarily college-aged and White, we conducted a pilot systematic review of peer-reviewed sexual consent literature to confirm this need. We then used structural equation modeling to test our proposed model with data from a national sample diverse regarding age and race/ethnicity ( n  = 589). We found that women's internal consent feelings are associated with their use of active consent cues—especially nonverbal cues. Because passive cues were unrelated to women's internal consent, not resisting or not saying no should not be used to infer women's consent.